Voices Not our Own - Doucette, Laurel (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 1993)
The underdevelopment of folklore studies in Canada can best be understood by examining the relevance of scholarly activity in the field to the Canadian academic milieu and, more broadly, to Canadian society. A feminist critique of the intellectual models and scholarly practices of folklore studies in Canada reveals that the activity continues to be influenced by several major intellectual constructs, namely modernization theory, colonialism, romantic nationalism, and structural functionalism; and that all of these combine to preserve cognitive models and power structures which impair the full participation of Canadian women ethnologists. Reclaiming the field of Canadian cultural studies requires the adoption of a new intellectual and attitudinal framework, one based on feminist principles of equality, inclusiveness, and empowerment, and grounded in experience, our own and that of the peoples whose cultures we study.